Impact of PCI strategies on outcomes of patients undergoing Transcatheter Aortic Valve Implantation with concomitant coronary artery disease: A systematic review and meta-analysis - Dayang Wang; Sijia Lai; Zichen Wang; Changbo Xuan; Xiaoxia Ren; Wenhua Peng; Guozhong Pan (PLoS ONE, 2025)
The aim of this study is to compare the clinical benefits associated with different percutaneous coronary intervention (PCI) timing strategies in patients undergoing transcatheter aortic valve implantation (TAVI) who have coexisting coronary artery disease (CAD). A systematic review and meta-analysis were conducted. PubMed, EMBASE, Cochrane Library and Web of Science databases were searched for relevant articles up to April 10th, 2024. Studies that reported comparisons of clinical outcomes between PCI before/concomitant with TAVI (PCI-TAVI) vs. TAVI alone, or comparisons between PCI before/concomitant with TAVI vs. PCI after TAVI (TAVI-PCI) were selected. Primary outcomes were all-cause mortality in the short-term, mid-term and long-term follow-up. A total of 23 studies pooling 15812 patients were included. Compared to TAVI alone, PCI-TAVI showed no significant difference in all-cause mortality at short- and mid-term (RRshort-term = 1.10 95%CI 0.88-1.38; RRmid-term = 1.12 95%CI 0.97-1.30), but an increase during long-term follow-up (RRlong-term = 1.20 95%CI 1.06-1.36). Compared with PCI-TAVI, TAVI-PCI is associated with lower rate of all-cause mortality at both short- and long-term follow-ups. PCI before or concomitant with TAVI may not offer clinical benefits and could potentially lead to worse outcomes in the long term. Conversely, PCI after TAVI is associated with improved clinical outcomes in both the short and long term.